Où s’arrête la famille ? Successions, droits d’appartenance et Bayt al-mâl à Alger à l’époque ottomane - Isabelle Grangaud (L'Atelier du CRH)
This article analyses the procedures of an Algerian Ottoman authority, the Bayt al-mâl, to support the defense claims of property in disinheritance. It considers some of the situations that show the reasons for it. In a first part the analysis focuses on the conditions of a transaction at the end of which Bayt al-mâl obtained the means to exercise these prerogatives. A second part analyses the intersecting logics of competing claims on properties without owner, showing that the authority of Bayt al-mâl as well as families and village or tribal communities confronted each other on this same ground in similar terms.